REDEFINING PHYSICAL ACTIVITY POST-COVID-19 TO IMPROVE THE QUALITY OF LIFE OF THE ELDERLY (CIPEEX, 2025)
This post-COVID-19 analysis demonstrates strategies to improve the quality of life of older adults, defined as citizens aged 60 years or older. The impacts of the pandemic on health and well-being are highlighted, emphasizing forms of prevention and rehabilitation. Guidelines for safe physical activity are recommended, considering the necessary precautions. Different techniques used for health recovery in the post-pandemic period are emphasized, highlighting the importance of integrating physical therapy into adapted exercise programs. These approaches are essential to meet the needs and limitations of older adults, thus promoting healthy aging. The analysis highlights the importance of continuous and personalized monitoring to ensure the effectiveness of the proposed interventions, ensuring that older adults can maintain an adequate level of physical activity, even in the face of restrictions imposed by the pandemic. The overall objective is to use scientific evidence to prove the benefits of physical activity in improving function, balance, mobility, and reducing the risk of falls for older adults.This research is a qualitative literature review, characterized by the collection of academic articles. The collection was carried out at the Ministry of Health through the Virtual Health Library (BVS), Google Scholar, Scientific Electronic Library Online (Scielo), and Periódico Capes (Capes Journals Portal).
Keywords: Physical activity; Quality of life of the elderly; Post-COVID-19